Global identification, structural analysis and expression characterization of cytochrome P450 monooxygenase superfamily in rice - Kaifa Wei; Huiqin Chen (BMC Genomics, 2018)
Abstract Background The cytochrome P450 monooxygenases (CYP450, CYP, P450) catalyze numerous monooxygenation/hydroxylation reactions in biochemical pathways. Although CYP superfamily has been systematically studied in a few species, the genome-scale research about it in rice has not been done. Results In this study, a total of 355 CYPs encoded by 326 genes were identified in japonica genome. The OsCYP genes are classified into 10 clans including 45 families according to phylogenetic analysis. More than half of the genes are distributed in 53 tandem duplicated gene clusters. Intron-exon structure of OsCYPs exhibits highly conserved and specificity within a family, and divergences of duplicate genes in gene structure result in non-functionalization, neo-functionalization or sub-functionalization. Selection pressure analysis showed that rice CYPs are under purifying selection. The microarray data analysis shows that some genes are tissue-specific expression, such as OsCYP710A5 and OsCYP71X14 in endosperm, OsCYP99A3 and OsCYP78A16 in root and OsCYP93G2 and OsCYP97D7 in leaf. Analysis of RNA-seq data derived from rice leaf developmental gradient indicates that some OsCYPs exhibit zone-specific expression patterns. OsCYP87C2, OsCYP96B5, OsCYP96B8 and OsCYP84A5 were specifically expressed in leaf base and transitional zone. The transcripts of lineages II and IV-1 members were highly abundant in maturing zone. Eighty three OsCYPs are differentially expressed in response to drought stress, of which OsCYP51G3, OsCYP709C9, OsCYP709C5, OsCYP81A6, OsCYP72A18 and OsCYP704A5 are strongly induced and OsCYP78A16, OsCYP89C9 and OsCYP704A5 are down-regulated significantly, and some of the results were validated by qPCR. And 23 up-regulated and 17 down-regulated genes are specific to Osbhlh148 mutation under drought stress. Compared to those in wild type, the changes in transcript levels of several genes are slight in the mutant, such as OsCYP51G3, OsCYP94C2, OsCYP709C9 and OsCYP709C5. Conclusion The whole-genomic analysis of rice P450 superfamily provides a clue to understanding biological function of OsCYPs in development regulation and drought stress response, and is helpful to rice molecular breeding.